Review on Selected Church Forests of Ethiopia: Implication for Plant Species Conservation and Climate Change Mitigation - Addisu Wolde (International Journal of Forestry Research)
Forests are known to play an important role in the conservation of biodiversity and regulation of global climate. Global climate is regulated through sequestering and storing much more carbon from the atmosphere due to the presence of forests. However, loss of forest cover and biodiversity due to anthropogenic activities are a growing concern in many parts of the world. The problem of deforestation and loss of biodiversity is more pronounced in developing countries like Ethiopia. Because of deforestation, the species diversity and climate mitigation potential of natural forests are going to be reduced. Thus, patches of Church forests are left and found throughout the degraded landscapes. Because of their religious significance, these forests have been conserved by local communities. They are the only refuge for different plant species and store high amounts of atmospheric carbon. This is due to local communities do have higher respect and trust in them than other local institutions, which has made the Church the central institution and platform for socio-economic issues of the people. As stated by different scholars, around the Church areas, numerous indigenous and International Union for Conservation of Nature red list species existed. In terms of the diversity of species, the forest around the Church has compared to that of a natural forest. Next to the conservation role, the conserved plant species have a significant contribution to climate change mitigation through carbon stock in biomass and soil. Trees in the Church areas have long life history and are higher in stand structure parameters such as height, diameter at breast height, crown diameter, and their carbon storage potential has been maximum. Overall, Church forests are serving as hot spot sites for biodiversity conservation and have a significant role in mitigating climate change by limiting greenhouse gas emissions and increasing the amount of carbon stored in forests.